1995
DOI: 10.1007/bf02246190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the spectrum of cognitive effects of alprazolam and adinazolam after single doses in healthy subjects

Abstract: Single doses of alprazolam (0, 0.5, 1.5 mg) or adinazolam mesylate sustained release tablets (SR) (0, 15, 45 mg) were administered to separate groups of 12 healthy men in a crossover design. Psychomotor performance was assessed by digit symbol substitution (DSST), and memory was assessed using a test battery which reflects various aspects of memory, including attention/working memory, explicit memory (recall of categorically related words), semantic memory (fragmented picture recognition, generation of categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In the present study, we aim to investigate biochemical and neurocognitive variables in patients with high anxiety levels associated with chronic stress, and neuroticism (a clinical condition that indicates an exaggerated response to the stressors that require more time to recover from them), 51 68 69 and the impact of intermediate-term treatment (12 weeks) with low doses of alprazolam.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we aim to investigate biochemical and neurocognitive variables in patients with high anxiety levels associated with chronic stress, and neuroticism (a clinical condition that indicates an exaggerated response to the stressors that require more time to recover from them), 51 68 69 and the impact of intermediate-term treatment (12 weeks) with low doses of alprazolam.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also suggested that benzodiazepines impair attention (Buffett-Jerrott et al 2003;Fleishaker et al 1995;Loke et al 1985;Rich et al 2006;Vidailhet et al 1994) which we also believe is implicated in the binding process (Diana and Reder 2006).…”
Section: What Do We Mean By "Binding"?mentioning
confidence: 67%
“…The severity of these effects tends to be dose dependent (Hommer, 1991). Numerous other cognitive functions have been reported to be negatively affected and include verbal fluency (Kirkby et al, 1995), psychomotor speed/performance (Allen, Curran, & Lader, 1991;Fleishaker, Garzone, Chambers, & Sirocco, 1995;Gorissen, Eling, van Luijtelaar, & Coenen, 1995;Seppala et al, 1980), reaction time , coordination and attention (Curran, Schiwy, & Lader, 1987;Hommer, Weingartner, & Breier, 1993;Seppala et al, 1980;Smimrne, Ferini Strambi, Pirola, & Tancredi, 1989), effortful processing (Joyce & File, 1995), episodic memory (Hege, Ellinwood, Wilson, & Helligers, 1997;Joyce et al, 1995;Mintzer et al, 2001), semantic memory (Massin-Krauss, Bacon, & Danion, 2002) and explicit memory (Curran, Gorenstein, & Lader, 1993;Hommer et al, 1993).…”
Section: Cognitive Effects Of Benzodiazepine Use Short-term Effectsmentioning
confidence: 99%